Polaron-assisted electronic transport in ZnP2 nanowires - de Oliveira, F. M.; Cabral, L.; Villegas-Lelovsky, L. [UNESP]; Lima, Matheus P.; Aragón, F. F.H.; Marques, G. E.; Chiquito, A. J.; Teodoro, M. D. (Royal Society of Chemistry (RSC), 2023)
In this work, carrier transport in a gold-seeded zinc diphosphide nanowire fabricated by vapor-liquid-solid and photolithography techniques is investigated in detail. The presence of zinc vacancies and interstitial phosphorus along the nanostructure resulted in defect levels evidenced by photoluminescence transitions observed in the near-infrared spectral range (800-900 nm). The electronic transport measurements by thermally stimulated current identified an activation energy of 80 meV, as well as a defect state with photoluminescence emission at 1.40 eV. The electronic transport in the transient regime was verified for temperatures below 50 K up to room temperature, and the photocurrent relaxation was described by a phenomenological model. We observed a well defined square-wave photoresponse of hundreds of nanoamperes per second during 532 nm light excitation, justifying the potential use of the device as a light sensor. Also, for the first time, ab initio calculations were performed considering defects of a Zn monovacancy close to an interstitial P atom to describe the luminescence transitions. The systematic use of a hybrid functional for these defects allows us to determine the presence of polarons due to the distortion of atomic bonds. Through the electronic property simulations, we corroborated the nature of p-type transport in zinc diphosphide nanowires.